Guide to the Solo Horn Repertoire - Dempf, Linda; Seraphinoff, Richard (Book collections on Project MUSE., 2016)
This comprehensive, annotated resource of solo repertoire for the horn documents in detail the rich catalogue of original solo compositions for the instrument. Intended as a guide for practical use and easy reference, it is organized into three large sections: works for unaccompanied horn, works for horn and keyboard, and works for horn and ensemble. Each entry includes publisher information, a brief description of the form and character of a work, technical details of the horn writing, and information on dedication and premiere. The authors also include commentary on the various techniques required and the performance challenges of each piece. Representing over ten years of careful compilation and notation by an expert in horn performance and pedagogy, and by a seasoned music librarian and natural horn performer, Guide to the Solo Horn Repertoire will be an invaluable resource for performers, educators, and composers [Publisher description].